Great Minds in Management: The Process of Theory DevelopmentGreat Minds in Management: The Process of Theory Development, edited by SmithKen G. and HittMichael A.. Oxford: Oxford University Press, 2005. - Nifadkar, Sushil S.; Tsui, Anne S. (Academy of Management Review, 2007)
This article presents a review of a book entitled ?Great Minds in Management: The Process of Theory Development,? edited by Ken G. Smith and Michael A. Hitt.